They Are Preserved Forever: Visualising the Memorialisation of Archipelagic Religious and Community Identities - James Moore (MDPI AG, 2021)
In this article, we respond to the Special Issue theme by addressing the complexities of religious identities in archipelagic communities where the dual role of the sea as conduit and barrier has impacted the parish system, farming estates and community life. The focus is primarily on nineteenth and twentieth century testimonies and material evidence, approached within a broader chronological context going back to the Middle Ages. Using qualitative GIS mapping of the habitations of the people memorialised in two burial grounds in Orkney, we visualise the active role of the islander in constructing identities linking people and place at parish, community and personal levels. The results show that the people with memorial stones were buried within a long-established parochial structure but did not adhere to ecclesiastical norms, with district burial grounds being favoured over a single parish churchyard. We conclude that this approach demonstrates the complexities of identities within an island community and identify its applicability in other contexts combining material culture and historical documentation to investigate religious island identities.